Structural Visualization of Manuscripts (StruViMan): Principles, Methods, Prospects - Dirkse, Saskia ca. 21. Jh. (Open theology, 2019)
This paper introduces a tool which offers scholars a new way to visualize the structure of manuscripts. The Structural Visualization of Manuscripts (or StruViMan) is a web-based application, developed as part of the Paratexts of the Greek Bible Project, a European Research Council project based in Munich. Drawing on the principles of structural codicology, StruViMan is able to translate the different stages of a manuscript’s development into a visual model based on the codex’s physical, historical layers and aims to facilitate the comparison of manuscripts. It can be used by any web-connected manuscript database from any cultural area and does not require the presence of electronic images. This presentation begins with a short survey of the principles underpinning the tool’s conception and development, followed by a demonstration of how manuscript data from both biblical and non-biblical Greek codices are transformed into interactive, customizable visualizations with varying display modes. We will also touch upon StruViMan’s technical aspects as an open-access web service, available to any software or database able to call its API using the correct parameters. We close with a preview of new features currently under development, including the ability to "reconstruct" a manuscript whose composite parts are presently in different repositories.